Curing the hiccup: Reforming administration of Islamic law in Malaysia - Shuaib, Farid Sufian (2009)
The earnest development of administration of Islamic law in Malaysia could be viewed as stemming from the desire to pick up the pieces left by the British and other colonial powers after their intervention in the Malay Archipelago. Intense Islamization in the Malay Sultanates was interrupted by the colonial intervention. After gaining her independence, efforts were made to strengthen derelict organisation of administration of Islamic law and to put back in the mainstream the marginalised Syariah court system. This paper looks at the development of administration of Islamic law within the context of the Malaysian legal system.